Hepatitis B and C among injecting drug users living with HIV in São Paulo, Brazil - Marchesini, Angela Mattos (2007)
OBJECTIVE: To describe the profile of injecting drug users living with HIV/AIDS and estimate hepatitis B and hepatitis C prevalence rates within this group. METHODS: Cross-sectional study conducted with 205 injecting drug users living with HIV/AIDS receiving attention in three public health clinics in the city of Sao Paulo, in 2003. A non-probabilistic sample of volunteers was selected consecutively on the days respondents appeared for their appointments at the clinics. Personal data and information on sexual behavior, drug use and knowledge of hepatitis was collected through interviews. Tests were conducted to detect infections of the hepatitis B and C viruses. RESULTS: Out of the interviewees, 81% were men and 19% women, with an average age of 39 (SD = 6.1) and six years of formal education (SD = 2.0). There was no difference in marital status between the sexes, of which 48% were single, 42% were married, and 8% were divorced. The average ages for first use of tobacco, alcohol and illegal drugs were 13, 15 and 18, respectively. Hepatitis B and C prevalence were 55% (95% CI: 49;63) and 83%(95% CI: 78;88), respectively. Eighty percent of respondents had not heard of Hepatitis B and C prior to the first time they used injecting drugs. CONCLUSIONS: The high prevalence rates of Hepatitis B and C and low level of knowledge regarding the diseases justify the inclusion of information about hepatitis infections and the hepatitis B vaccines in HIV harm reduction strategies.